The Effect of Consumer Attitude toward Functional Food on Package Attributes and Ingestion Intention; Focused on Garlic - Kyoung Kim, Hyun; Jeong Kim, Hyun; Jong Cha, Su (International Journal of Engineering and Technology, 2018)
The purpose of this study was to investigate the effect of prior knowledge and preference of garlic on the ingestion intention and selecting package attributes of garlic functional food. Surveys were conducted to verify the purpose of the study. One-way ANOVA was performed for data analysis; the following conclusions were reached.First, the prior knowledge and preference of garlic have a significant impact on the intention to ingest garlic functional food. Second, the prior knowledge and preference of garlic have a significant impact on the attitude toward package properties of garlic functional food.However, it was confirmed that the preference for garlic was a more significant influence on the selection of garlic functional food and garlic food packaging than the prior knowledge on the benefit of garlic. So this study casts significant implications for the marketing of functional food with strong flavors such as garlic.Â Â